Pengaruh Internalisasi Nilai-Nilai Pancasila dan Kecerdasan Spiritual terhadap Perilaku Prososial Siswa Buddhis: Systematic Literature Review (SLR) - Riasih Riasih; Partono Partono (Journal of Literature Review, 2026)
This study aims to analyze the influence of the internalization of Pancasila values and spiritual intelligence on the prosocial behavior of Buddhist students. The method employed was a Systematic Literature Review (SLR) of 50 selected articles obtained through systematic searching, screening based on inclusion–exclusion criteria, and citation chaining. The synthesis results indicate that the internalization of Pancasila values tends to be moderate to strong when integrated with spiritual and cultural dimensions, while spiritual intelligence functions as a mediator that deepens value internalization and promotes ethical behavior (Setiadi, 2019; Tumanggor et al., 2021; Untung et al., 2023). Prosocial behavior shows a positive correlation with value internalization and spiritual intelligence; however, it remains context-dependent and is not always sustained over time (Listiyaningsih et al., 2023; Rizkullah et al., 2024). Educational strategies based on experiential learning, reflection, and role modeling are proven to be more effective than normative–instructional approaches, particularly when contextualized within local cultural and religious frameworks (Solihah et al., 2020; Suroyo & Putra, 2024). The novelty of this study lies in its integrative synthesis, which positions spiritual intelligence as a mediating variable and educational strategies and cultural context as moderating variables in shaping prosocial behavior. These findings contribute to the development of a holistic and contextual framework for character education.